Weather Shocks and Output in Low-Income Countries : The Role of Policies and Adaptation - Acevedo Mejia, Sebastian (IMF Working Papers; Working Paper ;, 2019)
We explore the extent to which macroeconomic policies, structural policies, and institutions can mitigate the negative relationship between temperature shocks and output in countries with warm climates. Empirical evidence and simulations of a dynamic general equilibrium model reveal that good policies can help countries cope with negative weather shocks to some extent. However, none of the adaptive policies we consider can fully eliminate the large aggregate output losses that countries with hot climates experience due to rising temperatures. Only curbing greenhouse gas emissions-which would mitigate further global warming-could limit the adverse macroeconomic consequences of weather shocks in a long-lasting way.